A Study of the Determinants of Effective Relationship Marketing Practices on Organisational Growth in the Medium Sized Hotel Industry of Pakistan - Zahid, Umair; Tariq, Rizwan; Maqbool, Nosheen; Hussain, Mudassar; Khan, Junaid; Seuwou, Patrice (International Journal of Marketing Research Innovation, 2020)
The current study evaluates the determinants of effective relationship marketing (RM) practices on the organisational growth in the medium sized hotel industry of Pakistan. To attain the information about the topic, Hotel Days Inn has been selected. The current study has used the quantitative research design for obtaining the desired information. The developed survey questionnaire was distributed among the 273 customers of the Hotel Days Inn. In the study, a series of non-parametric tests like Chi-square, Descriptive analysis, and Spearman Rank Correlation was performed for quantitative findings. With the help of such statistical findings, it was observed that most of the research variables were taken into consideration due to their positive relationship with the organisational growth. That is, the Spearman correlation value for the customer satisfaction and organisational growth was calculated as 0.968 explaining the strong relation between the research variables. The developed research also displays different determinants for RM practices that has a direct influence on the organisational growth of the medium sized hotel industry of Pakistan. The acquired results of research also help the researcher in developing recommendations. These recommendations were based on the targeting practices of the hotels for attracting the customers and hiring of the trained and skilled staff that can positively influence the organisational growth and improve the RM practices.